Coiling followed by staged flow diversion for large and giant intracranial aneurysms - Lv, Nan; Ma, Hongyu; Zhou, Yu; Li, Zhiqing; Zeng, Yiyong; Li, Qiang; Zhao, Rui; Fang, Yibin; Yang, Pengfei; Huang, Qinghai; Hong, Bo; Xu, Yi; et al. (Frontiers in Neurology, 2022)
Objective: Delayed aneurysm rupture is a fatal complication after flow diversion treatment for large and giant intracranial aneurysms. This study aimed to investigate the feasibility and safety of coiling first and followed by planned flow diversion to prevent delayed aneurysm rupture. Methods: From January 2017 to December 2021 in two institutions, patients with unruptured intracranial aneurysms treated by coiling first and planned flow diversion were retrospectively collected. Data on demographic and aneurysmal characteristics, procedural details, and clinical and angiographic outcomes were reviewed. Results: Thirty-one patients were included (8 Males and 23 Females; Median age 58 years). Aneurysmal size ranged from 11.8-26.8 mm, with a median value of 18.4 mm. All aneurysms were located on the intradural segment of internal carotid arteries. Coiling and planned flow diversion were successfully performed in all patients. The time interval between coiling and flow diversion was 3.9-6.7 weeks, with a median value of 5.1 weeks. No hemorrhagic or ischemic complications occurred during the procedures and follow-up. Complete or subtotal occlusion was achieved in 87.1% (27/31) at the last angiographic follow-up (median 6.6 months). Conclusions: The preliminary data suggested that coiling unruptured intracranial aneurysms followed by planned flow diversion is both safe and effective. Further studies with larger cohorts are needed to verify the effect of this new strategy in preventing delayed rupture after flow diversion.